Mapping air pollution using Earth Observation techniques for cultural heritage sites - Agapiou, Athos; Nisantzi, Argyro; Lysandrou, Vasiliki; Mamouri, Rodanthi-Elisavet; Alexakis, Dimitrios; Themistocleous, Kyriacos; Sarris, Apostolos; Hadjimitsis, Diofantos G. (My University, 2013)
Air pollutants, together with climatic parameters, are of major importance for the deterioration of cultural heritage monuments. Atmospheric pollution is widely recognized as one of the major anthropogenic threats to architectural cultural heritage, in particular when associated with water absorption phenomena. Atmospheric particle deposition on surfaces of Monuments (of cultural heritage interest) may cause an aesthetic impact induced by a series of chemical reactions. Therefore there is a need for systematic monitoring and mapping of air pollution for areas where important archaeological sites and monuments are found. Earth observation techniques, such as the use of satellite image for the retrieval of Aerosol Optical Thickness (AOT), are ideal for this purpose. In this paper, all important monuments of the Paphos District, listed by the Department of Antiquities of Cyprus, have been mapped using Geographical Information Systems. Several recent (2012) MODIS satellite images (both Aqua and Terra) have been used to extract the AOT values in this area. Multi-temporal analysis was performed to identify areas of high risk where AOT values are considered to be high. In situ observations have been also carried out to verify the results.
Keywords: Air pollution; AOT; Cultural heritage; MODIS satellite; Paphos district